DETECTION OF GENETIC DETERMINANTS OF PATHOGENICITY OF STRAINS OF KLEBSIELLA SPP. ISOLATED FROM THE INTESTINAL BIOTOPE OF CHILDREN WITH FUNCTIONAL GASTROINTESTINAL DISORDERS - E. V. Grigorova; L. V. Rychkova; E. I. Ivanova; U. M. Nemchenko; M. V. Savelkaeva (Acta Biomedica Scientifica, 2018)
Functional gastrointestinal disorders (FGID) are one of the most common problems in children of the first year of life. The aim of the study was to assess the pathogenic potential of Klebsiella spp. strains, isolated from the colon in children of the first year of life with FGID. Material for the study included 61 coprological samples. The biological material was divided into comparison groups, depending on the type of Klebsiella excreted at a concentration of 105–108 CFU/g: 1st – with vegetation in the colon K. pneumoniae (n = 30); 2nd – with vegetation K. oxytoca (n = 31). Bacteriological study composition of the intestinal contents was carried out according to the Industry standard “Protocol of management of patients. Intestinal dysbiosis” (2003). Identification was carried out according to generally accepted schemes using commercial test systems for biochemical identification of bacteria. Statistical data processing was performed using licensed applications “MS Office Excel 2003 for Windows 7”. The data on the quantitative and qualitative changes in the composition microbiota in the comparison groups were obtained. The results of detection genetic determinants of pathogenicity in the samples of Klebsiella of two species show that among the strains of Klebsiella spp., vegetating in the intestines of children as a component of an allochthonous microbiota, a sufficiently high and virulent potential can be concentrated. Detection of pathogenicity genes in bacteria of the genus Klebsiella will expand and deepen the problem of finding the structures of adaptation of strains of bacteria that cause FGID in children of the first year of life.